2022
DOI: 10.3389/fpsyg.2022.894337
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Animation-Guided Mindfulness Meditation on the Promotion of Creativity, Flow and Affect

Abstract: Creativity is so important for social and technological development that people are eager to find an easy way to enhance it. Previous studies have shown that mindfulness has significant effects on positive affect (PA), working memory capacity, cognitive flexibility and many other aspects, which are the key to promoting creativity. However, there are few studies on the relationship between mindfulness and creativity. The mechanism between mindfulness and creativity is still uncertain. Meditation is an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 94 publications
1
18
0
Order By: Relevance
“…According to the broaden-and-build theory of positive emotions ( Fredrickson, 2001 ), mindfulness promotes the generation of positive emotions and further improves the cognitive flexibility and attention of individuals, thus expanding the scope of instant thinking and action of individuals and generating innovative behaviors. Previous studies have confirmed the mediating effect of positive emotions between mindfulness and creativity ( Chen et al, 2022 ). Based on this, we propose the following three hypotheses:…”
Section: Literature Review and Hypothesesmentioning
confidence: 57%
“…According to the broaden-and-build theory of positive emotions ( Fredrickson, 2001 ), mindfulness promotes the generation of positive emotions and further improves the cognitive flexibility and attention of individuals, thus expanding the scope of instant thinking and action of individuals and generating innovative behaviors. Previous studies have confirmed the mediating effect of positive emotions between mindfulness and creativity ( Chen et al, 2022 ). Based on this, we propose the following three hypotheses:…”
Section: Literature Review and Hypothesesmentioning
confidence: 57%
“…One approach considers flow a branch of mindfulness because both flow and mindfulness focus on one's awareness of the present moment. This approach has been supported in studies that examined how mindfulness helped individuals stay focused and maintain awareness of the present in various settings (Chen et al, 2019 , 2022a , b ; Liu et al, 2022b ). In contrast, another approach argues that flow and mindfulness are different from each other: mindfulness emphasizes one's self-awareness of his or her internal states, whereas an individual's self-awareness is largely weakened in the state of flow, due to an intense and focused concentration on the present (Reid, 2011 ).…”
Section: Discussionmentioning
confidence: 97%
“…Fifth, although flow is often considered an optimal experience that helps individuals regulate their emotions and improve their wellbeing (Chen et al, 2022b ), the role of flow in inducing problematic SVA use suggests its downside, which has been understudied in prior research. This reminds us to revisit flow in relation to mindfulness, a state of paying full attention to the present (Bishop et al, 2004 ; Regan et al, 2020 ; Liu et al, 2022a ) and keeping a non-judgmental awareness of one's internal experiences (Baer et al, 2006 ; Kabat-Zinn, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic has induced adolescents’ increased engagement on social media for multiple activities: work ( Liu et al, 2022e ), education ( Hsu et al, 2021 ), socialization (Liu et al, 2021), entertainment ( Chen et al, 2022a , b ), etc., which may influence parental intervention strategies. Our study focused on parental intervention in the post-pandemic era.…”
Section: Discussionmentioning
confidence: 99%